Global Climate Governance: A Legitimation Crisis - Van Vossole, Jonas (Review: A Journal of the Fernand Braudel Center, 2012)
This article frames the failure of COP19 in Warsaw, the problems of the RIO+20 summit, the failure of the Copenhagen COP15, and the problems of the carbon markets within a broader legitimacy crisis of global governance, a consequence of the crisis of the global capitalist socio-ecology. Two mechanisms give rise to the loss of legitimacy: unequal development and mercantilization, or the reconfiguration of the power balance and the destruction of social ties. As a consequence, both winners and losers contest the legitimacy of the institutions and mechanisms that govern global capitalism. In this article, we distinguish between Marx-type contestation, referring to emerging classes/states, and Polanyi-type contestation, referring to the victims of global mercantilization. As related to climate governance, the roles of the BRICs in climate negotiations and the global environmental justice movement represent these two types of contestation of the established organizational structures within the global capitalist socio-ecology.
Keywords: 21st century; BRICS countries - environmental conditions; BRICS countries - politics & government; MARX, Karl, 1818-1883; alienation; capitalism; climate governance; decision making in environmental policy; globalization & politics; history; organizational legitimacy; power (social sciences); research

A crise de legitimidade da governança climática global. Combinação de uma perspetiva marxista e polanyiana - Van Vossole, Jonas (2013)
This article frames recent problems of the RIO+20 summit, the failure of the Copenhagen Climate Change Conference (COP15) and the problems of the carbon markets within a broader legitimacy crisis of global governance, consequence of the crisis of the global capitalist socio-ecology. Two mechanisms give rise to the loss of legitimacy: unequal development and mercantilization, or the reconfiguration of the power balance and the destruction of social ties. As a consequence, both winners and losers contest the legitimacy of the institutions and mechanisms that govern global capitalism. In this article, we distinguish between the Marx-type of contestation, referring to emerging classes/states, and the Polanyi-type of contestation, referring to the victims of global mercantilization. In the case of climate governance, these winners and losers are represented by BRICS in climate negotiations and by the global environmental justice movement. (English)
Keywords: RIO+20; United Nations Conference on Sustainable Development (2012 : Rio de Janeiro, Brazil); capitalism; capitalisme; capitalismo; carbon dioxide mitigation; environmental aspects; environmental justice; gouvernance; governance; governança; international cooperation; international cooperation on climate change; international cooperation on environmental justice; international cooperation on environmental policy; justice environnementale; justiça ambiental; legitimacy; legitimation (sociology); legitimidade; légitimité